1975
DOI: 10.1111/j.1476-5381.1975.tb07353.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Kallikreins by Rat Kidney Slices

Abstract: 1Four radioactive kallikreins were isolated from rat kidney slices incubated with [3H -Lleucine.2 The kallikreins were purified by procedures previously used for the isolation of rat urinary kallikreins (Nustad & Pierce, 1974), and by affinity chromatography on a column of insolubilized anti-rat urinary kallikrein. 3 The kidney kallikreins resembled the urinary kallikreins in their relative amounts, isoelectric points and electrophoretic mobilities on polyacrylamide disc gels. 4 The data indicate that the kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…It preferentially acts on low molecular weight kininogen substrate to release lysyl-BK. Tissue kallikrein has also been reported to be present in plasma [22,23] Plasma kallikrein preferentially acts on high molecular weight kininogen substrate to release BK. BK promotes both cardiovascular and renal functions, for example, vasodilation, naturesis and diuresis [24,25] BK is rapidly (< 15 sec) inactivated by circulating kinases [26] BK acts on B1receptor (B1R) and B2 receptor (B2R) [27] to elicit physiological and pharmacological actions.…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 99%
“…It preferentially acts on low molecular weight kininogen substrate to release lysyl-BK. Tissue kallikrein has also been reported to be present in plasma [22,23] Plasma kallikrein preferentially acts on high molecular weight kininogen substrate to release BK. BK promotes both cardiovascular and renal functions, for example, vasodilation, naturesis and diuresis [24,25] BK is rapidly (< 15 sec) inactivated by circulating kinases [26] BK acts on B1receptor (B1R) and B2 receptor (B2R) [27] to elicit physiological and pharmacological actions.…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 99%
“…Renal kallikrein is synthesized by the kidney (Nustad et al, 1975) and has been found to be released into the urine and perfusion fluid of isolated perfused 'Author for correspondence. 2Present address: University of Tirana, Albania.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present study suggests that the elevation of circulating vasopressin levels induces a decrease in the synthesis of renal kallikrein. total kallikrein ; trypsinactivated kallikrein ; renal kallikrein system ; antidiuretic hormone Kallikrein is a serine protease which is synthesized by the kidney and excreted in the urine (Nustad et al 1975). It liberates kinins, potent vasodilator peptides, from its natural substrate kininogen.…”
mentioning
confidence: 99%